Regenerative Potential of Human Schneiderian Membrane: Progenitor Cells and Epithelial‐Mesenchymal Transition - Derjac‐Aramă, A.I.; Sarafoleanu, C.; Manea, C.M.; Nicolescu, M.I.; Vrapciu, A.D.; Rusu, M.C. (Anatomical record (Hoboken, N.J. : 2007), 2015)
ABSTRACT An innate osteogenic potential of the Schneiderian membrane (SM) is progressively assessed in studies ranging from non‐human species to human subjects. It has relevance for endosteal placement and osseointegration. Nestin‐expressing osteogenic progenitor cells are allegedly involved in bone formation and remodelling. Nestin phenotype was not assessed previously in human SM. We therefore aimed to fill that particular gap in the literature. Bioptic samples of human adult SM were obtained during surgery from eight adult patients, operated for non‐malignant pathologies. Immunohistochemistry on paraffin‐embedded tissue samples used primary antibodies against nestin, CD45, CD146, cytokeratin 7 (CK7), and alpha‐smooth muscle actin (α‐SMA). Nestin expression was consistently found in endothelial cells, and was scarcely encountered in pericytes, putative stromal stem/progenitor cells, as well as in glandular epithelial cells. Moreover, woven bone formation in the periosteal layer of the SM can also be regarded as evidence of the osteogenic potential of this membrane. Nestin and CD45 expression in cells of the primary bone supports the osteogenic potential of SM nestin‐expressing cells and a possible involvement of hematopoietic stem cells in maxillary sinus floor remodeling. CD146, a known inducer of epithelial‐mesenchymal transition (EMT), was expressed in epithelia, as was CK7. Isolated stromal cells were found expressing CD146, CK7 and α‐SMA, suggesting that regenerative processes happening in the SM may also involve processes of EMT which generate stem/progenitor cells. This study provides additional evidence for the regenerative potential of the Schneiderian membrane and identifies potential roles for cells of its stem niche in osteogenesis. Anat Rec, 298:2132–2140, 2015. © 2015 Wiley Periodicals, Inc.